Numerical taxonomic analysis in leaf architectural traits of some Hoya R. Br. species (Apocynaceae) from Philippines (Bangladesh Journal of Plant Taxonomy, 2016)
The present study examines the leaf variations in leaf traits of four Hoya R. Br. species from Philippines namely: (1) H. buotii Kloppenburg, (2) H. halconensis Kloppenburg, (3) H. mindorensis Schlechter red bearing flowers; and (4) H. mindorensis Schlechter yellow bearing flowers. Leaf samples (n= 30 leaves) were collected from each plant group and measured with nine architectural traits. The results showed variability in the leaves using univariate and multivariate analysis. Data ordination depicted variations in leaf morphology. The two plant groups H. mindorensis red bearing flowers and H. mindorensis yellow bearing flowers were consistently variable as supported by principal coordinate analysis, cluster analysis and two way Anova (P